Damage demand assessment of mainshock-damaged concrete gravity dams subjected to aftershocks. Issue 98 (July 2017) - Wang, Gaohui; Wang, Yongxiang; Lu, Wenbo; Yan, Peng; Zhou, Wei; Chen, Ming
Abstract: In China, the current seismic codes specify a single earthquake event as the design seismic load for concrete gravity dams. However, a large mainshock usually triggers numerous aftershocks in a short period. This paper assesses the effects of aftershocks on concrete gravity dam–reservoir–foundation systems and provides a quantitative description of the damage demands prior to and following the aftershocks. For this purpose, a set of 20 as-recorded mainshock–aftershock seismic sequences is considered in this study. The correlation between the ground motion characteristics of the as-recorded mainshocks and those of the aftershocks is examined. In order to identify the influence of the ground motion characteristics of aftershocks on the damage demands of the mainshock-damaged dams, the nonlinear behavior of the concrete gravity dams that are subjected to single seismic events and typical as-recorded seismic sequences is compared in terms of the structural damage, displacement response, and damage dissipated energy. A series of nonlinear dynamic analyses is performed to quantify the influence of aftershocks, which are selected by using different methods, on the damage demands of concrete gravity dam–reservoir–foundation systems in terms of the local and global damage indices. The results show that the aftershocks lead to an increase in the damage demands of the dam at the end of the seismic sequence when the concrete gravity dam is already damaged during the first individual seismic event and has not been repaired. In addition, the results also reveal that the repeated seismic sequences tend to underestimate the level of damage demands. Highlights: The effects of single aftershocks on damage demands of gravity dams are quantified. Ground motion characteristics of the mainshocks and aftershocks are discussed. The importance of aftershocks selected by different approaches is discussed. Repeated earthquakes tend to underestimate the damage demand level of gravity dams.